The role of high‐mobility group box protein 1 in collagen antibody‐induced arthritis is dependent on vascular endothelial growth factor. (19th January 2016) - Biscetti, F.; Flex, A.; Pecorini, G.; Angelini, F.; Arena, V.; Stigliano, E.; Gremese, E.; Tolusso, B.; Ferraccioli, G.
Summary: High‐mobility group box 1 (HMGB1) has been implicated in angiogenesis and rheumatoid arthritis (RA). The aim of this study was to define more clearly the role of HMGB1 in the synovial angiogenesis and pathogenesis of an immune model of arthritis. BALB/c mice were injected with monoclonal anti‐collagen antibody cocktail followed by lipopolysaccharide to induce arthritis. HMGB1 and vascular endothelial growth factor (VEGF) were over‐expressed in the areas of the synovium where more inflammation and neoangiogenesis were present. The selective blockade of HMGB1 or VEGF resulted alternatively in a lower severity of arthritis evaluated by the arthritis index. Furthermore, exogenous HMGB1 administration caused a worsening of arthritis, associated with VEGF up‐regulation and increased synovial angiogenesis. The selective inhibition of VEGF also resulted in no induction of arthritis in mice receiving exogenous HMGB1. Cytokine enzyme‐linked immunosorbent assay (ELISA) analyses performed on peripheral blood and synovial fluid demonstrated a significant reduction of interleukin (IL)−1β, IL‐6 and tumour necrosis factor (TNF)‐α in mice where HMGB1 and VEGF pathways were blocked. Interestingly, the selective blockade of HMGB1 and VEGF resulted in an increase of the peripheral IL‐17A concentration. The development of arthritis mediated by HMGB1 and the synovial angiogenesis can be blocked by inhibiting the VEGF activity. The proinflammatory and proangiogenic cytokine IL‐17A was increased when HMGB1 is inhibited, but the synovial angiogenesis was nevertheless reduced in this model of arthritis. Taken together, these findings shed new light on the role of this nuclear protein in the pathogenesis of arthritis in an RA‐like model.